Comparative evaluation of Platelet Rich Plasma (PRP) versus Platelet Rich Fibrin (PRF) scaffolds in regenerative endodontic treatment of immature necrotic permanent maxillary central incisors: A double blinded randomized controlled trial - Hazim Mohamed Rizk, Consultant; Mohamed Sherif Mohamed Salah Al-Deen, Professor; Asmaa Aly Emam, Lecturer (Saudi Dental Journal)
Objectives: The research aims to assess the regenerative potential of Platelet Rich Plasma (PRP) versus Platelet Rich Fibrin (PRF) scaffolds in immature permanent maxillary central incisors with necrotic pulps, clinically and radiographically. Trial design: Double blinded parallel randomized controlled trial was implemented to identify the results. Subject & methods: The proposed study was conducted among 30 patients with maxillary necrotic permanent immature central incisors but only 26 patients fulfilled the study requirements. Group I was treated with PRP and Group II with PRF scaffolds. Follow up has been done every 3 months for one year. Primary outcomes were measured clinically: Pain, Mobility, Swelling, and Sinus/fistula. Radiographically: increase root length and width. Secondary outcomes were clinically: Discoloration and Sensibility test. Radiographically: increase in bone density measurements and decrease in apical diameter. Standardized radiographs were collected during the follow up period, and radiographic changes were measured by using Image J software. Statistical analysis was performed on 25 patients who had completed the study. Results: All 25 patients' teeth were survived during the 12-month follow-up period. PRP showed marginal increase in radiographic root length and width, periapical bone density and a decrease in apical diameter. No statistical significant differences were observed when it was compared with PRF. The teeth which were treated did not respond to sensibility test at the end of the study. PRF displayed statistical significant higher amount of crown discoloration when compared to PRP group. Conclusions: For necrotic immature teeth, revascularization using PRP is an appropriate alternative to PRF and showed excellent 12-months prognosis.